2013
DOI: 10.1371/journal.pone.0074943
|View full text |Cite
|
Sign up to set email alerts
|

The Nociceptin/Orphanin FQ Receptor Antagonist UFP-101 Reduces Microvascular Inflammation to Lipopolysaccharide In Vivo

Abstract: Microvascular inflammation occurs during sepsis and the endogenous opioid-like peptide nociceptin/orphanin FQ (N/OFQ) is known to regulate inflammation. This study aimed to determine the inflammatory role of N/OFQ and its receptor NOP (ORL1) within the microcirculation, along with anti-inflammatory effects of the NOP antagonist UFP-101 (University of Ferrara Peptide-101) in an animal model of sepsis (endotoxemia).Male Wistar rats (220 to 300 g) were administered lipopolysaccharide (LPS) for 24 h (-24 h, 1 mg k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Endogenous N/OFQ function is also implicated in the response to systemic inflammation following lipopolysaccharide administration. Peptidic NOP receptor antagonist, UFP-101, has been shown to inhibit microvascular inflammation in vivo (Brookes et al, 2013), and we have shown that UFP-101 suppresses the hypothalamo-pituitary-adrenal (HPA) axis response to peripheral LPS challenge (Leggett, Dawe, Jessop, & Fulford, 2009). These findings are potentially of significant clinical relevance in the context that patients with more severe cases of sepsis have significantly higher concentrations of plasma N/OFQ and worse outcomes .…”
Section: Nociceptin and Nop Receptor: Relevance To Inflammationmentioning
confidence: 93%
“…Endogenous N/OFQ function is also implicated in the response to systemic inflammation following lipopolysaccharide administration. Peptidic NOP receptor antagonist, UFP-101, has been shown to inhibit microvascular inflammation in vivo (Brookes et al, 2013), and we have shown that UFP-101 suppresses the hypothalamo-pituitary-adrenal (HPA) axis response to peripheral LPS challenge (Leggett, Dawe, Jessop, & Fulford, 2009). These findings are potentially of significant clinical relevance in the context that patients with more severe cases of sepsis have significantly higher concentrations of plasma N/OFQ and worse outcomes .…”
Section: Nociceptin and Nop Receptor: Relevance To Inflammationmentioning
confidence: 93%
“…This indicates that enhanced plasma levels of nociceptin indicate continuation of the sepsis process [58] whereas a decrease in their levels may indicate recovery.…”
Section: Sepsis As a Pro-resolution Deficiency Disordermentioning
confidence: 99%
“…20 Furthermore, we showed that antagonising NOP with UFP-101 during LPS-induced sepsis produced anti-inflammatory effects (such as decreased macromolecular leak and reduced leucocyte rolling) in post-capillary venules.…”
Section: Studies Of the Nociceptin System During Sepsis In Animal Modelsmentioning
confidence: 84%
“…20 There is also evidence to suggest that N/OFQ may have the ability to recruit neutrophils directly.…”
mentioning
confidence: 99%